The cultural approach in the development discourse - MACIA MARTÍNEZ, Irene; DE ANGELIS, Alessia (Revista Iberoamericana de Estudios de Desarrollo)
We will try to analyse scope of the theoretical reflections making emphasis in the cultural element within the development discourse. Our analysis is carried out through a short study of different branches of Sociology and Anthropology interpretative perspectives regarding the development concept. Focusing the attention on cultural diversity, we want to analyse the presence of this matter in development policies. In the first place, we have carried out researches about the suitability of some universal values and its cross-cultural potential. Secondly, we have analysed how pluralism has shaped the development discourse and the language used for International Cooperation